Novel Mittag-Leffler stability of linear fractional delay difference equations with impulse. (August 2018) - Wu, Guo-Cheng; Baleanu, Dumitru; Huang, Lan-Lan
Abstract: In this letter we propose a class of linear fractional difference equations with discrete-time delay and impulse effects. The exact solutions are obtained by use of a discrete Mittag-Leffler function with delay and impulse. Besides, we provide comparison principle, stability results and numerical illustration.